Evaluation on nutritive value of four commercial Nile River fish species - Okuki, Obany; Goang, O.M.A,; Pio K Deng, (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2019)
The study was carried out to evaluate and assess the yield of edible, inedible parts and nutritional composition of four River Nile fish species. The fillets percentage yield was found to be 39.3±3.7%, 35.9±9.1%, 21.8±7.1%, and 37.14 % for Heterotis niloticus, clarias gariepinus, tetraodon lineatus, Malapterurus electricus respectively. Proximate analysis revealed that the protein was 20.3±0.07, 18.3±0.04, 18.1±0.08 and 19.3±0.08% for Heterotis niloticus, clarias gariepinus, tetraodon lineatus and Malapterurus electricus.  Fat content were 4.2±0.02%, 2.2±0.01%, 3.2±0.03% and 3.1±0.02% for Heterotis niloticus, clarias gariepinus, tetraodon lineatus and Malapterurus electricus respectively. Moisture content was found to be 74.0±0.02%, 77.8±0.08%, 77.3±0.01% and 76.4±0.03% respectively. And ash content was 1.5±0.06%, 1.7±0.06%, 1.3±0.04% and 1.3±0.02% respectively. Protein, fat, contents were significantly high in Heterotis niloticus, whereas moisture and ash contents were significantly high in clarias gariepinus. The study concluded that all species under investigation were rich in food nutritive value.